The Effect of Environmental Disclosure and Green Innovation on Firm Value - Ahmad Rifqi Hidayat (International Journal of Management Science and Information Technology, 2025)
This study aims to analyze the effect of environmental disclosure and green innovation on firm value. The research employs a quantitative approach using correlation analysis and panel data regression, assisted by EViews 12 software. The data consist of secondary data obtained from the annual financial reports of 20 companies listed on the Indonesia Stock Exchange during the 2020–2024 period, resulting in 100 observations. The empirical results indicate that environmental disclosure has a significant positive effect on firm value, while green innovation does not show a significant influence. These findings suggest that transparent environmental disclosure plays a crucial role in enhancing firm value by strengthening investor confidence. Practically, this study provides insights for investors in evaluating corporate sustainability performance and encourages companies to improve the quality of their environmental disclosures and green innovation strategies to support long-term sustainability and value creation.